Politics according to the Bible : a comprehensive resource for understanding modern political issues in light of Scripture - Grudem, Wayne A. (Grand Rapids, MI : Zondervan, 2010)
A comprehensive political philosophy, arguing for Christian involvement based on biblical teachings and a Christian worldview. --from publisher description
Basic principles. Five wrong views about Christians and government ; A better solution : significant Christian influence on government ; Biblical principles concerning government ; A biblical worldview ; The courts and the question of ultimate power in a nation -- Specific issues. The protection of life ; Marriage ; The family ; Economics ; The environment ; National defense ; Foreign policy ; Freedom of speech ; Freedom of religion ; Special groups -- Concluding observations. The problem of media bias : when the watchdogs fall asleep ; Application to Democratic and Republication policies today ; Faith and works, and trusting God while working in politics and government.
Includes bibliographical references and indexes.
Keywords: Political science -- Philosophy; Politics in the Bible; Bible and politics; Christianity and politics; Church and social problems